40. Immunofluorescent intraepidermal nerve fiber normal density at distal leg: A multicenter study. Issue 4 (April 2016) - Provitera, V.; Gibbons, C.H.; Wendelchafer-Crabb, G.; Donadio, V.; Vitale, D.F.; Stancanelli, A.; Caporaso, G.; Liguori, R.; Wang, N.; Santoro, L.; Kennedy, W.R.; Nolano, M.
Abstract : We created an age and gender adjusted normative dataset for intraepidermal nerve fiber (IENF) density at distal leg in skin samples processed with immunofluorescence. We collected from four experienced laboratories worldwide IENF density data of 528 healthy individuals. Skin samples were collected, processed and analyzed according to standard procedures. We employed quantile regression analysis to tailor the fit of the 5° percentile as the normal cut-off value and to measure the effect of age, gender, body mass index (BMI), and race as possible influential variables. Age and sex showed an independent linear correlation with IENF density. For each decade, the 5° quantile cut-off showed a 0.54 fibers/mm decrease, while females exhibited a 1.0 fibers/mm cut-off greater than males. BMI didn't affect IENF counts and we did not find significant differences between Caucasian and non-Caucasian subjects although our cohort was not suitable to draw definitive conclusions on this issue. In conclusion, we presented for the first time an age and gender adjusted normative dataset for intraepidermal nerve fiber density at distal leg obtained with indirect immunofluorescence by sharing data from four experienced laboratories worldwide. This dataset can be used as reference for laboratories processing skin biopsies with this technique.